Measuring shear and compression wave velocities of soil using bender-extender elements - Leong, Eng Choon (2011)
Piezoceramic elements have been used for laboratory measurement of wave velocity in soil and rock specimens. Shear-wave piezoceramic elements (bender elements) are commonly used to measure shear wave velocity for the determination of small-strain shear modulus. Compression-wave piezoceramic elements (extender elements), on the other hand, are less commonly used as compression wave velocity is less frequently measured. In this paper, the performance of a pair of bender–extender elements for the determination of both shear and compression wave velocities is examined with respect to the resolution of the recorder, bender–extender element size. and excitation voltage frequency. The evaluation showed that the performance of the bender–extender elements test can be improved by considering the following conditions: (i) the digital oscilloscope used to record the bender–extender element signals should have a high analog to digital (A/D) conversion resolution; (ii) the size of the bender–extender elements plays an important role in the strength and quality of the receiver signal, especially for compression waves; and (iii) using a wave path length to wavelength ratio of 3.33 enables a more reliable determination of shear wave velocity.